P Pengaruh Growth, Leverage, Profitabilitas, Free cash flow, Dan Kepemilikan Institusional Terhadap Manajemen Laba Pada Perusahaan Sektor Keuangan Yang Terdaftar Di BEI - I Putu Suwidi Astawa; Ni Kadek Sinarwati (Vokasi : Jurnal Riset Akuntansi, 2024)
Profit management is the act of managing the company's financial statements through the selection of certain accounting policies with the aim of increasing net profit and company value in accordance with management expectations. This study aims to analyze the effect of growth, leverage, profitability, free cash flow, and institutional ownership on profit management. This research was conducted on financial sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The sampling method of this study is by purposive sampling in accordance with predetermined criteria and obtained samples of 53 companies. The data in this study is secondary data derived from financial statements that have been published during the research year. The results of the analysis show that partial growth, leverage, profitability, free cash flow have a positive effect on profit management, this means that the higher the partial growth, leverage, profitability, free cash flow, the profit management practice will increase. While institutional ownership negatively affects profit management, this means that the more institutional ownership increases, the lower the profit management action.